看護師の研究活用の障壁と教育的支援によって変化可能な影響要因 - 塚越 徳子; 岡 美智代; 京田 亜由美; 瀬沼 麻衣子; 近藤 由香; 松本 光寛; 梨木 恵実子; 深澤 友子; 齋藤 明香; 高橋 さつき; 國清 恭子; 内田 陽子; et al. (日本看護科学会誌, 2023)
要旨　目的：看護師の研究活用の障壁と教育的支援によって変化可能な影響要因を明らかにする．　方法：A大学病院の看護師とA県内医療・福祉機関に所属もしくはA大学院修了の専門看護師計860名を対象に質問票調査を行った．研究活用の障壁を従属変数，看護研究への態度，臨床実践力，看護研究に関する経験を独立変数とする重回帰分析を行った．　結果：295名を分析対象とした．障壁が高かった因子は「研究活用の組織的支援」であった．重回帰分析の結果，全変数を投入したモデル1と教育的支援によって変化可能な変数を投入したモデル2では，回帰式の適合度にほぼ差がなかった．肯定的な看護研究への態度，専門性の高い看護実践，看護研究の指導経験がある看護師は障壁が少なかった．　結論：研究活用の障壁は，基本属性を除く教育的支援によって変化可能な変数で説明可能であった．影響要因として，看護研究の態度，臨床実践力，看護研究の指導経験が示された． 　Objective: To clarify barriers to nurses' research utilization and determine factors that can be influenced through educational support.　Method: A total of 860 nurses were the study participants, consisting of hospital nurses and certified nurse specialists working in medical and welfare institutions. A questionnaire survey was conducted with participants. A multiple regression analysis was then performed with barriers to research utilization as the dependent variable and attitudes to nursing research, professional practice skills, and experience with nursing research as independent variables.　Result: Questionnaire responses from 295 participants were analyzed. The factor with the highest barrier was "organizational support for research utilization". Multiple regression analysis revealed that nurses with positive attitudes to nursing research, highly professional practice skills, and experience in teaching nursing research experienced fewer barriers. There was no difference in the goodness of fit of the regression equations between Model 1, which included all variables, and Model 2, which included variables that can be influenced through educational support.　Conclusions: Barriers to research utilization could be explained by variables that can be influenced through educational support. Attitude toward nursing research, professional practice skills, and experience in teaching nursing research were shown as influencing factors.